Analysis of the profile of primary school teacher candidates' readiness in the context of teachers' professional competencies: Students' self-reflection - Maria Melani Ika Susanti (Universitas Negeri Surabaya, 2026)
The readiness of prospective teachers is a key factor in ensuring the quality of education at the elementary school level. However, the existing literature often places too much emphasis on the mastery of technical skills, while neglecting the internal professional identity that is formed through self-reflection. This study aims to analyze the readiness profile of prospective elementary school teachers within the framework of four professional competencies namely, the pedagogical, professional, personal, and social domains while identifying the subjective meaning of the teaching profession through students’ self-symbolization. A descriptive approach with a sequential explanatory mixed-methods design was employed. Quantitative data were collected from seventh-semester PGSD students via a validated 30-item Likert-scale questionnaire, followed by qualitative data collection through observation and narrative reflection. Quantitative results indicate a high level of readiness, with average scores of 4.03 for pedagogical competence, 4.14 for professional competence, and 4.20 for personal competence, while social competence achieved a very high score of 4.50. Qualitative findings reveal that students demonstrate readiness by applying innovative models such as PjBL and integrating digital tools based on HOTS. Additionally, symbolic reflections such as the coconut tree and the candle illustrate that students view teaching as a transformative calling that requires resilience and dedication. This study fills a research gap by linking standardized competency assessments with symbolic self-reflection. The findings suggest that teacher education institutions should integrate reflective practices into their curricula to strengthen professional identity beyond academic mastery. This study presents a new diagnostic framework for assessing teacher readiness through a combination of psychometric data and in-depth qualitative insights.